2003
DOI: 10.1007/s00415-003-1010-7
|View full text |Cite
|
Sign up to set email alerts
|

Cause and course in a series of patients with sporadic chorea

Abstract: Although a convincing concordance between choreic signs and neuroradiological findings was possible in 4 patients only, it was possible to assign an aetiology in most cases with vascular related causes the most frequent and metabolic factors often participating. Huntington's disease is not unusual as a cause of sporadic choreas. HIV infection is an emerging cause of chorea and AIDS-related disease should be considered in young patients presenting without a family history of movement disorders. We emphasize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 29 publications
(28 reference statements)
4
53
1
4
Order By: Relevance
“…The HD is a more common presentation compared to others. The HIV infection (specially, no family history of movement disorders in younger), vascular causes and drugs are not common (2,3).…”
Section: Dear Editormentioning
confidence: 99%
“…The HD is a more common presentation compared to others. The HIV infection (specially, no family history of movement disorders in younger), vascular causes and drugs are not common (2,3).…”
Section: Dear Editormentioning
confidence: 99%
“…The other genetic conditions causing chorea (Table 20.2) are quite rare. One study of consecutive patients with non-genetic forms of chorea seen at a tertiary hospital found that stroke accounted for 50% of all cases, drug abuse was identified in one-third of the patients, while the remaining patients had chorea related to AIDS and other infections, as well as metabolic problems (Piccolo et al, 2003).…”
Section: Clinical Presentation and Prevalencementioning
confidence: 99%
“…Aside levodopa-induced chorea in Parkinson's disease, cerebro-vascular disease is the most common cause of non-genetic chorea (Piccolo et al, 2003). Nevertheless, chorea is an unusual complication of acute vascular lesion, seen in less than 1% of patients with acute stroke .…”
Section: Vascular Choreasmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found various ischemic, and one hemorrhagic, lesions in 21 of 51 (41%) consecutive cases of sporadic chorea. 3 Some of these lesions were in basal ganglia or thalami but they were thought to be the cause of chorea in only two patients. Carotid duplex ultrasonography was not reported so it is possible that some had undetected carotid artery stenosis.…”
mentioning
confidence: 98%